Peran digital marketing terhadap minat beli pada Tiktok Shop dimediasi electronic word of mouth - Bagas, Stio; Nurfarida, Iva Nurdiana; Hidayat, Candra Wahyu (MBR (Management and Business Review), 2023)
The research investigates the influence of digital marketing on purchase intention, and investigates the role of electronic word of mouth (e-WOM) as a mediator. The research was conducted on TikTok shop users in Malang City and took 120 people as research samples, data was collected using a questionnaire, and Path Analysis was carried out for hypothesis testing. The analysis results reveal that digital marketing influences consumer buying interest. Purchase intention is also influenced by e-WOM. However, digital marketing does not have a significant impact on e-WOM, thus e-WOM does not have a mediating role in the influence of digital marketing on the buying interest of Tiktok shop users.